Identifying a novel cuproptosis-related necroptosis gene subtype-related signature for predicting the prognosis, tumor microenvironment, and immunotherapy of hepatocellular carcinoma - Shi, Yuanxin; Qiu, Peng; Zhao, Kai; Li, Xiangyu; Feng, Yunxiang; Deng, Zhengdong; Wang, Jianming (Frontiers in Molecular Biosciences, 2023)
Background： Cuproptosis and necroptosis represent two distinct programmed cell death modalities implicated in neoplastic progression, however, the role of combining cuproptosis and necroptosis in hepatocellular carcinoma (HCC) remain to be elucidated. Methods： A total of 29 cuproptosis related necroptosis genes (CRNGs) were identified, followed by an extensive analysis of their mutational characteristics, expression patterns, prognostic implications, and associations with the tumor microenvironment (TME). Subsequently, a CRNG subtype related signature was developed, and its value of prognostic prediction, TME and therapeutic responses in HCC were thoroughly investigated. Lastly, quantitative real-time PCR (qRT-PCR) and Western blotting (WB) were employed for investigating the signature genes expression of in 15 paired clinical tissue samples. Results： Two distinct CRNG subtypes were discerned, demonstrating associations between CRNG expression patterns, clinicopathological attributes, prognosis, and the TME. A CRNG subtype related prognostic signature, subjected to external validation, was constructed, serving as an independent prognostic factor for HCC patients, indicating poor prognosis for high-risk individuals. Concurrently, the signature's correlations with an immune-suppressive TME, mutational features, stemness properties, immune checkpoint genes, chemoresistance-associated genes, and drug sensitivity were observed, signifying its utility in predicting treatment responses. Subsequently, highly accurate and clinically convenient nomograms were developed, and the signature genes were validated via qRT-PCR and WB, further substantiating the stability and dependability of the CRNG subtype related prognostic signature. Conclusion： Overall, this investigation presented an extensive panorama of CRNGs and developed the CRNG subtype related prognostic signature, which holds potential for implementation in personalized treatment strategies and prognostic forecasting for HCC patients.